Children's conservation ability as related to some variables its implications for mathematical education - Rivero, Lina Diaz 1947- (1979)
This study was concerned with the development and acquisition of certain science/mathematics concepts: length, area and volume. Sixty randomly selected children from Grades 4-6 with ages 10-12 years were involved in the study. Four conservation tasks were used as research instruments. Findings of the study showed that the environment had no significant effect on the achievement of conservation of the children in the study; there was a sequential development of conservation of length, area, and volume in this order; and it was observed from the data that the process of transition from one stage to another is gradual and proceeds at different rates for each child for each task.